A herança patrimonialista no processo sucessório de empresas familiares no Brasil - Faria, Celso Bruno (2014)
The succession topic of family businesses in Brazil has been the subject of many studies, research and scholarly articles, given the importance of this issue in the Brazilian organizational reality. The present study addressed this issue by identifying the complex web of meanings that surround the succession process in family businesses in Brazil. Thus, the present study examined the manifestation of traits in patrimonial succession process of Brazilian companies, describing and analyzing a set of family firms the presence of patrimonial succession process orientation in these organizations. The choice of cases was guided by criteria of convenience of the researcher, specifically, among relatives of the Fluminense region companies where their leaders were willing to participate in such a study. In the case of an analytic-descriptive research subjectivist orientation, was chosen as the design of this work multi-case study. Work answered the question about the proposed to describe and analyze the extent to which, in cases of succession in family businesses chosen for the study, there is a dash of Brazilian companies patrimonial purpose. Showed a predominance of patrimonial aspects of orientation, although to identify certain elements of how it manifests differently in some companies.